A novel theoretical analysis of quadruple pass Erbium doped fiber amplifier - Naji, Ahmed Wathik; Mohammed, M. A.; Zaidan, A. A.; Zaidan, B. B.; Al-Khateeb, Wajdi Fawzi Mohammed; Al-Khateeb, Khalid A. Saeed; Mahdi, Mohd Adzir (Academic Journals, 2011)
A novel theoretical analysis model of dual stage quadruple pass (DSQP) Erbium-doped Fiber Amplifier (EDFA) is presented in this paper. This analysis is carried out by the broad input signal power starting from -50 to 0 dBm input signal with 10 to 220 mW pumping powers. The EDFA has been proposed and demonstrated by using an optical circulator and tunable band pass to reflect signal in each stage with a two level pump scheme through EDF length 10 and 15 m in the first and the second stage, respectively. The design parameters of EDFA are optimized using the numerical simulation of EDFA rate equations model in order to optimize the performance of EDFA. Finally, a comparative analysis is conducted to compare results of the theoretical modeling and the published experimental results. The comparative analysis showed that the proposed theoretical model has similar results compared to published experimental results.